Tillid: En emotionel relation i pædagogprofessionen - Krøjer, Jo (Tidsskrift for Professionsstudier, 2017)
A new study explores how professional knowledge are shaped in the relation between pedagogues and parents in kindergartens. It is well known that the care work of professional pedagogues holds emotional aspects as in integrated part of professional, pedagogical know-how. Opposed to what you might think, these emotional aspects of pedagogues’ work in this study seems not to be exclusively related to caregiving for children, on the contrary: Emotions also arises from relations with parents. This article examines this unexpected finding. How come that relations between professional pedagogues and kindergarten parents are carrying such a heavy, emotional load? And what are the implications of this for the pedagogical profession? The relevance of these questions is to expand the understanding of emotional demands in professional, pedagogical work in institutional caregiving practices.